Marfan Syndrome: Regarding Two Cases - Elsy Roxana Geroy Moya; María Quiñones Hernández; Anaelys Acosta Hernández (Revista Finlay)
Marfan syndrome is an autosomal dominant genetic disorder, with a prevalence of 1 every 5,000-10,000 newborns, so it is classified as an uncommon disease. It affects multiple organs and systems; its prognosis is marked by the cardiovascular involvement. Multidisciplinary follow-up of these patients allows the timely diagnosis of complications and improves their quality of life. Two cases with Marfan syndrome and other associated diseases are presented. A literature review was carried out regarding the report of 2 teenager clinical cases with suggestive phenotypic characteristics, the first case with an associated arachnoidocele and the second case with Gilbert's disease.